Pengaruh Metode Kangguru terhadap Penurunan Suhu Tubuh, Frekuensi Menyusu dan Durasi Tidur Bayi - Ritonga, Nikmah Jalilah; Sitorus, Riris; Pulungan, Susi Andriany (Jurnal Riset Hesti Medan, 2021)
Immunizations sometimes have side effects once they are given to babies. DPT immunization is one that has a low-grade fever side effect and sometimes results in high fever and seizures. One of the efforts to treat fever in infants is the kangaroo method. Through this method, heat transfer occurs between mother and baby, increasing the frequency of breastfeeding which can meet the fluid needs of the feverish baby and facilitate the baby in increasing the duration of quiet sleep, less crying and less activity. The purpose of this study was to determine the effect of the kangaroo method on decreasing body temperature, feeding frequency and infant sleep duration. Sampling using Porbability Sampling with Simple Random Sampling technique, totaling 30 people and divided into 2 groups of 15 people each, namely the experimental and control groups. The results of the analysis are based on several assumptions of One way MANOVA, namely there is linearity between variables, the data is normally distributed, multicollinearity is not detected and the covariance matrix between groups is assumed to be the same as the Box'M value p = 0.006 > 0.001. The results of the multivariate test showed that there was a significant difference between the two groups with a value of F (3.26) = 49.334, p< 0.001; Wilk’s ʌ 0.149, ƞp2 = 0.851, then the univariate results showed that group differences caused significant differences in body temperature, feeding frequency and sleep duration with p < 0.001. The results of the bonferroni correction further test showed that the average decrease in body temperature, feeding frequency and duration of infant sleep in the experimental group was better than the control group with p < 0.001. This study proves that the kangaroo method has an effect on decreasing body temperature, breastfeeding frequency and infant sleep duration after DPT immunization.